Evaluation of larvicidal effects of five different tropical plant extracts against filarial vector Culex quinquefasciatus - Islam, Mohammad Robiul; Akter, Samima; Nasiruddin, Munira; Awal, Mohammad Abdul; Haider, M. Mahathir (International Journal of Research in Medical Sciences, 2025)
Background: The aim of the study was to assess the larvicidal activity of leaf extracts of Sphaegneticola trilobata, Syzygium cumini, Averrhoa carambola, Tamarindus indica and Citrus maxima. Methods: The 3rd and 4th instar larva of Culex quinquefasciatus were tested to evaluate larval mortality after 24-hour exposure to different plant leaf extracts. Larvicidal activity of S. trilobata leaf extract, S. cuimini, A. carambola, T. indica, Culex quinquefasciatus, and C. maxima leaf was observed at different concentrations of distilled water (1250-10000 ppm), acetone (250-850 ppm), methanol (2000-3500 ppm) and 50% ethanol (3000-5000 ppm). Results: Larval mortality was checked after 24h of exposure and lethal concentrations at LC50 of S. trilobata were 4183.866 ppm, 486.109 ppm, 2478.026 ppm, 3541.842 ppm respectively and at LC90 were 11717.896 ppm, 908.933 ppm, 3321.521 ppm, 4892.513 ppm respectively. Lethal concentrations of S. cuimini at LC50 were 9045.301 ppm, 476.714 ppm, 1797.028 ppm, 2825.363 ppm respectively and at LC90 were 14411.664 ppm, 1070.723 ppm, 2433.824 ppm, 4211.212 ppm respectively. And, for A. carambola lethal concentrations at LC50 were 8405.722 ppm, 927.011 ppm, 2080.519 ppm, 4977.002 ppm respectively and at LC90 were 13438.102 ppm, 1455.087 ppm, 3020.974 ppm, 6165.633 ppm respectively. For T. indica, application dosage was 7038.103 ppm, 565.073 ppm, 1739.942 ppm, and 3876.449 ppm. Again, for Culex quinquefasciatus larvae, the larvicidal LC50 values of C. maxima leaf extract at the application dosage are 2931.936 ppm, 633.329 ppm, 1306.784 ppm, and 1710.784 ppm respectively. Conclusions: These results indicate the potential of the phytochemicals derived from experimental plants.